Hubungan Implementasi Clinical Governance dengan Pencegahan Sengketa Medis di Rsud Wangaya Denpasar - A. A. Intan Pramesti; Ida Ayu Uttari Priyadarshini; Putu Tiara Mas Pracinti Ariesta Putri; Putu K. Helsayani; I Gede Yudhistira Cahaya Dinata (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the relationship between the implementation of clinical governance and the prevention of medical disputes at Wangaya Regional Public Hospital, Denpasar. A quantitative analytical approach with a cross-sectional design was employed. Data were collected through questionnaires distributed to approximately 30 healthcare professionals, including doctors, nurses, and other medical staff using a Likert scale (1–5). This study can be considered a preliminary study (pilot project) due to the relatively limited sample size (n=30). The results indicate that the implementation of clinical governance is categorized as good, reflected in high compliance with clinical standards, effective supervision, and structured risk management systems. The quality of healthcare services is also perceived as very good, particularly in terms of patient safety, communication, and professionalism. Furthermore, healthcare workers show a strong agreement that high-quality services can significantly reduce the risk of medical disputes.Statistical analysis reveals a significant and positive relationship between clinical governance and the prevention of medical disputes (r = 0.65; p < 0.05). Regression analysis shows that clinical governance has a significant effect on dispute prevention, with a coefficient of 0.72 and a determination value of 42%. This implies that improved clinical governance contributes substantially to reducing potential conflicts between healthcare providers and patients.In conclusion, clinical governance serves as an effective preventive strategy in minimizing medical disputes while enhancing the quality and safety of healthcare services.